Open and closed pantalar dislocations: A systematic review - Joseph R Brown, DPM; Zachary P Hill, DPM; Tucker Peabody, DO; Benjamin C Taylor, MD (Foot & Ankle Surgery: Techniques, Reports & Cases, 2024)
Pantalar dislocations are a relatively rare traumatic condition of the foot and ankle, and outcomes are overall unknown for these patients. A systematic review was performed to identify articles evaluating outcomes following treatment of pantalar dislocations. Studies with a minimum of 1 year follow-up, with mention of patient reported outcome measures (PROMs) and complications were included. The mean complication rate, secondary operation rate, and PROM scores were calculated based on the included articles. 203 articles were initially identified. 15 articles met the inclusion criteria, for a total of 62 pantalar dislocations. All studies were level 4 evidence (i.e., case study or series). Open dislocations (40/62; 65%) were more common than closed dislocations (22/62; 35%). The most common form of treatment of open reduction with external fixation (n = 12). The average follow-up was 43.02 months for the entire cohort. The mean age was 37.3 (19-81) years and most patients were male (n = 43). Complication rates were relatively high, with 30.6% (19/62) having osteonecrosis, 17.7% (11/62) having arthritis, and 11.3% (7/62) experiencing an infection. 19.4% (12/62) of patients required a secondary operation. At a minimum 1 year follow up, the pooled mean AOFAS and FFI scores were 75.8 and 37.5, respectively. High complication rates can be expected with relatively poor functional outcomes at short term follow up with pantalar dislocations secondary to the traumatic nature of these injuries. Surgeons managing lower extremity trauma should be aware of this pathology and treatment strategies.Level of Evidence: Level 3 Systematic Review